Coordination of horizontal and vertical alignment of a two-lane highway by computer graphics - Esguerra, George D.; Jones, John Hugh; Prapansak Buranaprapa; Prinzl, Frediric; Royal Thai Government(King's Scholarship) (Bangkok : Asian Institute of Technology, 1982)
This Research dealt with the interactive generation and plotting of perspective views of two-lane roads for coordination of horizontal and vertical alignment for highway geometric design. An IBM 3031 Model-6 computer and a Watanabe Plotter WX625 as the graphic device were used. The computer programs developed enabled the computation of highway alignment elements, the generation of space coordinates, the transformation of the spatial coordinates into perspective picture plane coordinates with the observer at any arbitrarily selected location, and the plotting of the perspective views. Emphasis was placed on the use of computer-drawn perspective to correct alignment defects and unsafe features that could result from separately considering the horizontal alignment and longitudinal profile.
Thesis (M. Eng.) - Asian Institute of Technology, 1982
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Keywords: Roads -- Design